Uncertainties shaping parental educational decisions: The case of Syrian refugee children in Turkey - Karaagac, Dilara; Bilecen, Basak; Veenstra, René (Frontiers in Human Dynamics, 2022)
Around a million school-aged minors from Syria have been living in Turkey with temporary protection status over an unanticipated extended period. This prolonged temporariness leads to uncertainties and unpredictabilities for Syrian families regarding how long they will be staying in Turkey. Drawing on 17 interviews with Syrian mothers and 3 couples, this study examined the ways in which uncertainties shaped parental decisions on minors’ education. The findings indicated that uncertainties played a key role in shaping the educational decisions of Syrian parents, particularly in their children’s Turkish language acquisition and educational performance. This study not only fills the gap in understanding the effects of uncertainties in parental educational decisions emanated from a prolonged temporariness, but also argues that living in an uncertain context causes hurdles in language acquisition which has major educational and social consequences for children.